1994
DOI: 10.1002/micr.1920150808
|View full text |Cite
|
Sign up to set email alerts
|

A rabbit ear model for cold stress testing

Abstract: A rabbit ear model resembling the human digit was studied to determine the vascular response of the rabbit ear to a cold stress. Following moderate cooling (10 minutes at 5 degrees - 8 degrees C), auricular blood flow and cutaneous perfusion were reduced. This decrease was reversed by 30 minutes of warming. The response in the rabbit ear to cold stress is similar to that of normal human digits. The similarities between the control of the circulation in human digits and rabbit ears may result from the similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The rabbit ear model permits dircct microvascular observations of arteriovenous anastomoses (19). Following a cold thermal stress, the auricular circulation in normal rabbits is characterized by an overall reduction in blood flow in the ear and cutancous perfusion similar to that observed in human digits (22). Recent in vivo studies of the rabbit have identified specific receptor innervation of the ear microvasculature, with a,-adrenoceptor control predominating over arteriovenous anastomosis regulation (18).…”
mentioning
confidence: 99%
“…The rabbit ear model permits dircct microvascular observations of arteriovenous anastomoses (19). Following a cold thermal stress, the auricular circulation in normal rabbits is characterized by an overall reduction in blood flow in the ear and cutancous perfusion similar to that observed in human digits (22). Recent in vivo studies of the rabbit have identified specific receptor innervation of the ear microvasculature, with a,-adrenoceptor control predominating over arteriovenous anastomosis regulation (18).…”
mentioning
confidence: 99%
“…This system allows the dual microvascular functions of maintenance of tissue nutrition (through the capillaries) and temperature regulation (through the arteriovenous anastomoses) (5). Thermoregulatory blood vesscls of the skin mediate homeostasis of body temperature by dilating in response to heating and constricting in response to cooling (19). Dilation of the arteriovenous anastomoses causes warm blood from the arterial circulation to pass into the deep venous plexus of the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical instrumentation procedures were performed as described previously. 21 Briefly, a transit time flow probe (model 1 RB; Transonic Systems, Inc., Ithaca, NY) was placed around the central auricular artery near the base of the ear. The electrical connector was passed under the skin across the cranium and held within an anchor button sutured to the rabbit's skin.…”
Section: Instrumentation Techniquesmentioning
confidence: 99%
“…One week after instrumentation, the rabbits were subjected to a three-phase testing procedure. 21 Baseline measurements were recorded for 20 minutes at ambient room temperature (23 to 25°C) to complete the first phase of this testing procedure. The rabbits were then placed in a cooling unit (5 to 8°C) for 10 minutes to determine their physiological response to a cold stress test.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation